Relationship of coating factor of coated tubular electrodes for hardfacing by SMAW process, with the consumption parameters and the geometry of the deposited metal. - Cruz Crespo, Amado; Scotti, Américo; Fernández Fuentes, Rafael; Ortiz Méndez, Tamara (Revista Técnica da Faculdade de Engenharia da de Zulia, 2013)
At the present paper it is reported the relationship of coated factor in the behavior of coated tubular electrodes for hardfacing, using SMAW process, as to consumption parameters and the geometry of the deposited metal. The tubular electrodes were made with two coating thickness for a fixed diameter of the metal tube and coating composition, in order to value the exclusive influence of the coating thickness. Each coating factor (relation between the total diameter of the electrode and the diameter of the metal tube) was evaluated as a function of the variation in welding current. Deposits over the metal plate were made, let- ting evaluate the geometrical dimensions of the welding bead and the consumption parameter of electrodes. Based on the obtained results was concluded that for those electrodes the value of the coating factor have to be 1,2 and showing the best integral performance around an average welding current of 100 A.